Occurrence of Eimeria Schneider, 1875 species in feedlot lambs - Rahal, N. M. [UNESP]; Meireles, M. [UNESP]; Baptista, R. S. [UNESP]; Denadai, D. S. [UNESP]; Bovino, F.; Feitosa, F. L. F. [UNESP]; Peiro, J. R. [UNESP]; Mendes, L. C. N. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
This study describes the Eimeria Schneider, 1875 species that occurred in a lamb feedlot, as well as the dynamics of oocyst output in the environment and its correlation with daily weight gain (DWG) and climatic variables during nine weeks. One hundred and four lambs of various breeds and crossbreeds, at approximately 60 days old, were placed in a feedlot and submitted to periodic weighing and clinical and coprological evaluations. Fecal samples presenting more than 500 Eimeria spp. oocysts per gram (OPG) were separated for sporulation, and oocysts were identified at species level. Among evaluated oocysts, the following species were identified: E. parva, E. crandallis, E. ovinoidalis, E. weybridgensis, E. bakuensis, E. marsica, E. ahsata, E. granulosa, E. pallida and E. faurei. Eimeria crandallis was the most frequent one, being identified in 44 of the 58 evaluated samples, while E. parva was the more abundant in individual counts in most weeks. None of the animals presented clinical signs of eimeriosis and negative correlation coefficients were found for OPG vs DWG (-0.075) and OPG vs rainfall, as for OPG vs temperature this coefficient was positive. Animals shedding oocysts presented mixed infection, with up to seven species parasitizing the same lamb.
Keywords: ovine; oocysts; eimeriosis; OPG